Cibercuiabania na folkcomunicação política: Estudo da campanha eleitoral de 2016 para prefeito pelo Partido Socialismo e Liberdade em Cuiabá - Silvia Ramos Bezerra (Revista Internacional de Folkcomunicação, 2017)
This article aims to discuss the use of folkcomunication strategies in PSOL (Party Socialism and Freedom) 2016´s electoral campaign of for the position in the City Hall in Cuiabá. Such strategies can be better understood under the notion, still in development by these authors, of cybercuiabania. We can preliminarily define cybercuiabania as the set of cybercultural interventions produced through the incorporation of elements of popular culture and folklore of the Cuiabá macro-region, Mato Grosso. We chose, for the sake of illustration in this work, two advertising pieces of the said electoral campaign: the logo and the main jingle.